War Wounds — Changing Concepts - Nagpal, BM (Med J Armed Forces India, 2002)
The accepted standard treatment of war wounds through the last century has been debridement and delayed primary closure. However, recently, there has been a renewed Interest In primary closure of these wounds. 1481 war wounds were managed by the authors and out of 789 soft tissue injuries, 389 (47%) were closed primarily (group 1) after meticulous debridement and 220 (28%) underwent delayed primary closure (group 2). The infection rate in group 1 was 4.87% compared to 6.36% in group 2. The average hospital stay in group 1 was 15 days, significantly shorter by 10 days than in group 2. In the war zone both time and resources are at a premium and primary closure of selected wounds offers a better alternative to delayed primary closure.